Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
ISBN 978-91-85735-17-4
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais